The Effect of Resistance Training on Motor Unit Firing Properties: A Systematic Review and Meta-Analysis - Elgueta-Cancino, Edith; Evans, Ethan; Martinez-Valdes, Eduardo; Falla, Deborah (Frontiers in Physiology, 2022)
While neural changes are thought to be responsible for early increases in strength following resistance training (RT), the exact changes in motor unit (MU) firing properties remain unclear. This review aims to synthesise the available evidence on the effect of RT on MU firing properties. MEDLINE (OVID interface), EMBASE (OVID interface), Web of Science (all databases), Cochrane Library, EBSCO CINAHL Plus, PubMed and EBSCO SportDiscus were searched from inception until June 2021. Randomised controlled trials and non-randomised studies of interventions that compared RT to no intervention (control) were included. Two reviewers independently extracted data from each trial, assessed the risk of bias and rated the cumulative quality of evidence. Motor unit discharge rate (MUDR), motor unit recruitment threshold (MURT), motor unit discharge rate variability (MUDRV), MU discharge rate at recruitment versus recruitment threshold relationship, and MU discharge rate versus recruitment threshold relationship were assessed. Seven trials including 167 participants met the inclusion criteria. Meta-analysis (four studies) revealed that MUDR did not change significantly (P= 0.43), but with considerable heterogeneity likely to be present (I2 =91). Low to moderate evidence supports changes in MUDRV, MUDR at recruitment versus recruitment threshold relationship, and the MUDR versus recruitment threshold relationship. Overall, this systematic review revealed that there is a lack of high-quality evidence for the effect of RT on MU firing properties. Heterogeneity across studies undermines the quality of the evidence for multiple outcomes and affects the conclusions that can be drawn.